2015
DOI: 10.1542/peds.2014-1386
|View full text |Cite
|
Sign up to set email alerts
|

Online Problem-Solving Therapy After Traumatic Brain Injury: A Randomized Controlled Trial

Abstract: BACKGROUND: Pediatric traumatic brain injury (TBI) contributes to impairments in functioning in everyday settings. Evidence suggests that online family problem-solving therapy (FPST) may be effective in reducing adolescent behavioral morbidity. This article examines the efficacy of Counselor-Assisted Problem Solving (CAPS), a form of online FPST in improving long-term functional outcomes of adolescents with TBI relative to Internet resources only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 38 publications
0
67
0
Order By: Relevance
“…problem-solving and emotional dysregulation) noted minimal behavioural changes immediately post-intervention [58, 93,98,100,104,105,107]. However there was high participant satisfaction with using tele-practice [93] and greater changes observed in outcome at follow-up [58, 98,100,104,105,107].…”
Section: Telerehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…problem-solving and emotional dysregulation) noted minimal behavioural changes immediately post-intervention [58, 93,98,100,104,105,107]. However there was high participant satisfaction with using tele-practice [93] and greater changes observed in outcome at follow-up [58, 98,100,104,105,107].…”
Section: Telerehabilitationmentioning
confidence: 99%
“…Indeed, telerehabilitation for MANUSCRIPT ACCEPTED -BRAIN INJURY: 02 FEBRUARY 2017 17 people with TBI featured in 38 of the included papers (see Table 2), comprising 2 systematic reviews [39,79], 22 group comparison trials [23][24][25]30,35,52,58,74,77,82,84,[98][99][100][104][105][106][108][109][110][111]113], 9 case series [28,50,80,83,93,97,101,102,107] Importantly, no statistically significant differences were found between the tele-practice and face-to-face intervention delivery methods [39,79].…”
mentioning
confidence: 99%
“…Parent-and teen-reported time spent on the websites did not differ significantly by group. 18 Within the CAPS group, 35% of parents were single (n = 23), 23% (n = 15) were married with only one parent participating, and 41% (n = 27) were married with both parents participating. Among participants assigned to CAPS, 32 were attending high school and 33 were attending middle school at baseline.…”
Section: Participantsmentioning
confidence: 97%
“…For example, we found that both child’s age and family SES moderated treatment effects, with older adolescents and families of lower SES benefiting more from the online problem-solving treatments. 4,5 Furthermore, it is sometimes difficult to determine if cognitive and behavioral problems that developed post TBI are directly related to the injury or if the problems would have developed later regardless of the brain injury (e.g., Attention Deficit Hyperactivity Disorder). Developmental and age considerations may significantly impact decisions around trial design, recruitment/enrollment, outcome selection, and interpretation of findings.…”
Section: Developmental and Age Considerationsmentioning
confidence: 99%
“…Our single study with a narrower time-window post injury (1–7 months) revealed some initial treatment effects but others that emerged over the course of 12 month follow-up. 4,15 Our experiences suggest that the timing of intervention matters, with early versus late intervention having different sets of challenges. Intervention development, delivery, and assessment must account for timing of intervention delivery (early versus late recovery) to maximize the relevance and benefit for families.…”
Section: Timing Of Intervention Deliverymentioning
confidence: 99%